Fenton-like catalysts for efficient reduction of Fe(III) and their preparation and application

By using hydrothermal and high-temperature carbonization processes in Fenton-like catalysts, tourmaline with conductive carbon on the surface was prepared, which solved the problems of low Fe3+ reduction efficiency and large iron sludge generation in the prior art, and achieved the effect of efficient reduction and pollutant removal.

CN115888728BActive Publication Date: 2025-05-02浙江省环境科技股份有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211525018.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-05-02
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The existing Fenton-like catalysts cannot reduce Fe3+ in a timely and efficient manner, resulting in a large amount of iron sludge.

Method used

By conducting hydrothermal reactions with tourmaline at a specific temperature and then carbonizing at a high temperature, tourmaline with conductive carbon on the surface is prepared, thereby achieving efficient reduction of Fe(III).

Benefits of technology

This method significantly improves the reduction efficiency of Fe3+, reduces the amount of iron sludge, and the removal rate of sulfathiazole reaches 93.46% under the condition of pH 5.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115888728B_ABST
    Figure CN115888728B_ABST
Patent Text Reader

Abstract

The present invention discloses a Fenton-like catalyst capable of efficiently reducing Fe(III), and a preparation method and application thereof. The preparation method comprises: uniformly dispersing glucose and tourmaline in water, transferring the obtained mixed solution to a reactor for hydrothermal reaction; the temperature of the hydrothermal reaction is 160-180°C; carbonizing the dried product after the hydrothermal reaction at 480-500°C under the protection of an inert gas to obtain a tourmaline having conductive carbon on the surface, which is a Fenton-like catalyst capable of efficiently reducing Fe(III). The tourmaline having conductive carbon on the surface prepared by the present invention can be used for efficiently reducing Fe(III) and removing sulfathiazole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of Fenton-like catalysts, and in particular to a Fenton-like catalyst capable of efficiently reducing Fe(III) and a preparation method and application thereof. Background Art

[0002] Fenton-like technology is an advanced oxidation technology developed from the traditional homogeneous Fenton, in which homogeneous reactions and heterogeneous reactions coexist in the same reaction system. In this technology, the solid-phase catalyst replaces the ionic iron catalyst in the traditional Fenton, reducing the amount of iron sludge generated and broadening the applicable pH value for the Fenton system to treat pollutants.

[0003] The Chinese patent application with application number CN202110958312.3 discloses a one-step synthesis of hydrothermal carbon-loaded iron oxalate ore and its preparation method, which loads hydrothermal carbon on the surface of iron oxalate ore by hydrothermal method, and reduces Fe(III) in the iron oxalate ore to Fe(II) during the hydrothermal process, which helps the subsequent Fenton reaction. However, the Fe(III) and oxalic acid ligands formed after the catalyst is put into the system and reacts with H2O2 require additional light to be reduced to Fe(II) again.

[0004] Tourmaline is a common natural mineral, and its crystal structure enables tourmaline to convert mechanical energy into electrical energy. The Chinese patent application with application number CN202110689879.5 discloses a magnetic Fenton catalyst and its preparation method and application, which loads magnetic Fe3O4 on the tourmaline surface by coprecipitation to achieve trivalent iron reduction during the reaction. However, due to insufficient electron sources in this system, trivalent iron cannot be effectively reduced. Therefore, it is necessary to develop a Fenton-like catalyst that can continuously and efficiently reduce trivalent iron and reduce the formation of iron sludge in the system. Summary of the invention

[0005] In view of the above technical problems and the shortcomings in the art, the present invention provides a method for preparing a Fenton-like catalyst that can efficiently reduce Fe(III), which can solve the problem that the existing Fenton-like catalyst cannot timely and efficiently reduce Fe 3+ , technical problems of producing large amounts of iron sludge.

[0006] The specific technical solutions are as follows:

[0007] A method for preparing a Fenton-like catalyst capable of efficiently reducing Fe(III) comprises the steps of:

[0008] (1) Glucose and tourmaline are uniformly dispersed in water, and the resulting mixed solution is transferred to a reactor for hydrothermal reaction; the temperature of the hydrothermal reaction is 160-180° C.;

[0009] (2) The dried product after the hydrothermal reaction is carbonized at a high temperature of 480-500° C. under the protection of an inert gas to obtain tourmaline with conductive carbon on the surface, which is a Fenton-like catalyst for the efficient reduction of Fe(III).

[0010] The invention uses glucose and tourmaline as raw materials, and prepares a Fenton-like catalyst capable of efficiently reducing Fe(III) through hydrothermal treatment at a specific temperature and high-temperature carbonization. The preparation method is simple and the cost is low.

[0011] The inventors have found that if glucose and tourmaline are directly mixed and carbonized at high temperature without going through a hydrothermal reaction process, a carbonization temperature of 800-900°C is required to make the glucose form conductive carbon. Too high a carbonization temperature will cause the tourmaline lattice and structure to be destroyed, rendering the tourmaline ineffective.

[0012] Based on this, the inventors first adopted a hydrothermal reaction process at a specific temperature to make glucose condense under a certain temperature and high pressure conditions. The dried product after the hydrothermal reaction can be carbonized at 480-500°C to form tourmaline with conductive carbon on the surface, and the carbonization temperature conditions will not cause damage to the tourmaline lattice and structure.

[0013] In a preferred example, in the method for preparing a Fenton-like catalyst that can efficiently reduce Fe(III), in step (1), the mass ratio of glucose to tourmaline is 1-3:3, and more preferably 2:3, which can obtain the optimal interface electric field strength and fully demonstrate the electron donating ability of the conductive carbon.

[0014] In a preferred embodiment, in the method for preparing the Fenton-like catalyst capable of efficiently reducing Fe(III), in step (1), the concentration of tourmaline in the mixed solution is 150-200 g L -1 .

[0015] In a preferred embodiment, in the method for preparing the Fenton-like catalyst capable of efficiently reducing Fe(III), in step (1), the particle size of the tourmaline is less than 10000 mesh, which is beneficial to improve the material's catalytic activity against Fe(III). 3+ restoration capability.

[0016] In a preferred embodiment, in the method for preparing the Fenton-like catalyst capable of efficiently reducing Fe(III), in step (1), the hydrothermal reaction time is 8-12 hours.

[0017] In a preferred embodiment, in the method for preparing the Fenton-like catalyst capable of efficiently reducing Fe(III), in step (2), the inert gas is a rare gas and / or nitrogen.

[0018] In a preferred embodiment, in the method for preparing the Fenton-like catalyst capable of efficiently reducing Fe(III), in step (2), the heating rate of the high-temperature carbonization is 5-10°C min -1 .

[0019] In a preferred embodiment, in the method for preparing the Fenton-like catalyst capable of efficiently reducing Fe(III), in step (2), the high-temperature carbonization time is 2-3 hours.

[0020] The present invention also provides tourmaline with conductive carbon on the surface prepared by the preparation method of the Fenton-like catalyst capable of efficiently reducing Fe(III).

[0021] The Fenton-like catalyst of the present invention is prepared by modifying or loading conductive carbon on the surface of tourmaline. The conductive carbon provides electrons to increase the Fe 3+ The reduction efficiency can effectively reduce Fe 3+ Fe 2+ The reduction efficiency can reach 87.01%, which can reduce the amount of iron sludge produced.

[0022] The invention also provides application of the tourmaline with conductive carbon on the surface in reducing Fe(III).

[0023] As a general inventive concept, the present invention also provides the use of the tourmaline having conductive carbon on the surface as or for preparing a Fenton-like catalyst in wastewater treatment.

[0024] The Fenton-like catalyst of the present invention can achieve a removal rate of 93.46% for sulfathiazole at a pH value of 5 through the mechanism of adsorption synergistic catalytic degradation, which is conducive to the promotion of practical applications.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention prepares a Fenton-like catalyst capable of efficiently reducing Fe(III) by hydrothermal treatment at a specific temperature and high-temperature carbonization. The preparation method is simple and low in cost. Glucose and tourmaline are used as raw materials. Conductive carbon capable of providing electrons is formed on the surface of the tourmaline while retaining the original lattice and structure of the tourmaline, thereby efficiently reducing Fe 3+ Fe 2+ , significantly increased Fe 3+ Improve the reduction efficiency and reduce the amount of iron sludge produced.

[0027] Moreover, the Fenton-like catalyst of the present invention has a good removal effect on sulfathiazole and has practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The particle size of tourmaline is related to Fe 3+Impact diagram of reduction capacity.

[0029] Figure 2 This is a comprehensive thermal analysis diagram of tourmaline passing through a 10,000 mesh sieve.

[0030] Figure 3 This is a scanning electron microscope photograph of the Fenton-like catalyst prepared in Example 1.

[0031] Figure 4 The Fenton-like catalyst prepared in Example 1-3 and the original tourmaline sieved through 10000 mesh were used for Fe 3+ Effect diagram of the reduction ability of .

[0032] Figure 5 This is a scanning electron microscope photograph of the Fenton-like catalyst prepared in Example 2.

[0033] Figure 6 This is a scanning electron microscope photograph of the Fenton-like catalyst prepared in Example 3.

[0034] Figure 7 This is a high-resolution transmission electron microscopy photograph of the Fenton-like catalyst prepared in Example 3.

[0035] Figure 8 This is a diagram showing the removal effect of sulfathiazole by the Fenton-like catalyst prepared in Example 3 at a pH value of 5. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0037] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or conditions recommended by the manufacturers.

[0038] The inventors first studied the effect of tourmaline on Fe 3+ 0.3 g of tourmaline sieved through 325 mesh, 2000 mesh and 10000 mesh was added to 100 mL of ultrapure water with a pH value of 3 and stirred at a speed of 300 rpm. Then 300 μmol L -1 Fe 3+ (refers to the initial Fe 3+ The concentration is 300 μM, the anion is sulfate ion, the same below), and the stirring is continued for 60 min. The reduced Fe 3+ , the results are as follows Figure 1 As shown, tourmaline with different mesh sizes reduces Fe 3+ Fe 2+ The ability of the smallest tourmaline to reduce Fe3+ The reduction capacity is the strongest, because the interfacial electric field generated by tourmaline when it is stirred is greater with smaller size. The reduction capacity is 25.51±0.57μmol L -1 , but the reduction rate is only 8.50%, which still needs to be further improved.

[0039] Before modifying tourmaline, the inventors first determined the temperature that tourmaline crystals could withstand through comprehensive thermal analysis. Figure 2 As shown in the figure, the tourmaline passing through a 10000 mesh sieve has two endothermic peaks at 713.2°C and 903.7°C, with mass losses of 2.30% and 2.32% respectively. This is because the tourmaline undergoes a phase change at high temperatures and releases the OH groups in the crystal structure. According to the comprehensive thermal analysis results, the crystal structure of tourmaline will not undergo a phase change below 500°C.

[0040] Example 1

[0041] The preparation method of the Fenton-like catalyst of the present embodiment is carried out according to the following steps:

[0042] (1) Weigh 2 g of glucose and 6 g of tourmaline sieved through a 10,000 mesh sieve, mix well, add to 30 mL of ultrapure water, and stir magnetically at 300 rpm for 30 min;

[0043] (2) pouring the mixture into a reactor and carrying out a hydrothermal reaction at a reaction temperature of 170° C. for 10 h;

[0044] (3) The dried product after the hydrothermal reaction was placed in a vacuum tube furnace and carbonized at high temperature under a nitrogen atmosphere at a heating rate of 5 °C min -1 , the carbonization temperature is 500°C, and the insulation time is 2.5h to finally obtain tourmaline with conductive carbon on the surface.

[0045] The scanning electron microscope photo of the Fenton-like catalyst prepared in Example 1 is as follows: Figure 3 As shown, from Figure 3 It can be seen that the Fenton-like catalyst is irregularly shaped particles, and due to the polar effect of tourmaline, small particles tend to agglomerate onto the surface of large particles.

[0046] 0.3 g of the Fenton-like catalyst prepared in Example 1 was added to 100 mL of ultrapure water with a pH value of 3 and stirred at a speed of 300 rpm. 300 μmol L -1 Fe 3+ After continuing to stir for 60 minutes, Figure 4 It can be seen that the system reduces Fe 3+ Fe 2+ The amount was 191.86 μmol L -1, indicating that the conductive carbon on the tourmaline surface provides electrons to Fe 3+ , efficient regeneration of Fe 2+ .

[0047] Example 2

[0048] The preparation method of the Fenton-like catalyst of the present embodiment is carried out according to the following steps:

[0049] (1) Weigh 6 g of glucose and 6 g of tourmaline sieved through a 10,000 mesh sieve, mix well, add to 30 mL of ultrapure water, and stir magnetically at 300 rpm for 30 min;

[0050] (2) pouring the mixture into a reactor for hydrothermal reaction at a temperature of 180° C. for 8 h;

[0051] (3) The dried product after the hydrothermal reaction was placed in a vacuum tube furnace and carbonized at high temperature under a nitrogen atmosphere at a heating rate of 5 °C min -1 , the carbonization temperature is 500℃, and the insulation time is 3h to finally obtain tourmaline with conductive carbon on the surface.

[0052] The scanning electron microscope photo of the Fenton-like catalyst prepared in Example 2 is as follows: Figure 5 As shown, from Figure 5 It can be seen that the Fenton-like catalyst is irregularly shaped particles, and due to the polar effect of tourmaline, small particles tend to agglomerate onto the surface of large particles.

[0053] 0.3 g of the Fenton-like catalyst prepared in Example 2 was added to 100 mL of ultrapure water with a pH value of 3 and stirred at a speed of 300 rpm. 300 μmol L -1 Fe 3+ After continuing to stir for 60 minutes, Figure 4 It can be seen that the system reduces Fe 3+ Fe 2+ The amount was 121.06 μmol L -1 , indicating that the conductive carbon on the tourmaline surface provides electrons to Fe 3+ , efficient regeneration of Fe 2+ .

[0054] Example 3

[0055] The preparation method of the Fenton-like catalyst of the present embodiment is carried out according to the following steps:

[0056] (1) Weigh 4 g of glucose and 6 g of tourmaline passed through a 10,000-mesh sieve, mix well, add to 30 mL of ultrapure water, and stir magnetically at 300 rpm for 30 min;

[0057] (2) pouring the mixture into a reactor for hydrothermal reaction at a temperature of 160° C. for 12 h;

[0058] (3) The dried product after the hydrothermal reaction was placed in a vacuum tube furnace and carbonized at high temperature under a nitrogen atmosphere at a heating rate of 5 °C min -1 , the carbonization temperature is 500℃, and the insulation time is 2h to finally obtain tourmaline with conductive carbon on the surface.

[0059] The scanning electron microscope photo of the Fenton-like catalyst prepared in Example 3 is as follows: Figure 6 As shown, from Figure 6 It can be seen that the Fenton-like catalyst is an irregularly shaped particle, and due to the polar effect of tourmaline, small particles tend to agglomerate onto the surface of large particles. Figure 7 As shown, the high-resolution transmission electron micrograph of the Fenton-like catalyst prepared in Example 3 shows the (101) crystal plane of tourmaline and the (002) crystal plane of conductive carbon (graphite), verifying that the conductive carbon has been coated on the surface of tourmaline.

[0060] 0.3 g of the Fenton-like catalyst prepared in Example 3 was added to 100 mL of ultrapure water with a pH value of 3 and stirred at a speed of 300 rpm. 300 μmol L -1 Fe 3+ After continuing to stir for 60 minutes, Figure 4 It can be seen that the system reduces Fe 3+ Fe 2+ The amount was 261.04 μmol L -1 , indicating that the conductive carbon on the tourmaline surface provides electrons to Fe 3+ , efficient regeneration of Fe 2+ Example 3: The Fenton-like catalyst prepared by Fe 3+ The reason why the reduction rate is the highest is that the coating amount of conductive carbon in Example 1 is insufficient to provide sufficient electrons to the system, but the excessive coating of conductive carbon in Example 2 reduces the interfacial electric field strength, thereby limiting the electron donating ability of carbon.

[0061] The concentration is 5 mg L -1 100 mL of sulfathiazole solution was prepared, the pH value was adjusted to 5, and 0.3 g of the Fenton-like catalyst prepared in Example 3 was added. First, a 30 min adsorption experiment was performed to investigate the adsorption capacity of the Fenton-like catalyst for sulfathiazole, and then 5 mmol L -1 H2O2, and a Fenton-like reaction was carried out for 60 min. The results are shown in Figure 8 After 30 minutes of adsorption, the removal rate of pollutants by the catalyst reached 39.12%, and after 60 minutes of Fenton-like reaction, the overall removal rate reached 93.46%.

[0062] From the above examples, it can be seen that the Fenton-like catalyst prepared by the present invention can effectively reduce Fe 3+ Fe 2+ , which can reduce the formation of iron sludge and is suitable for promotion to actual water treatment processes.

[0063] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a Fenton-like catalyst capable of efficiently reducing Fe(III), characterized in that: Includes steps: (1) Glucose and tourmaline are uniformly dispersed in water, and the resulting mixed solution is transferred to a reactor for hydrothermal reaction; the temperature of the hydrothermal reaction is 160-180° C., and the time of the hydrothermal reaction is 8-12 hours; the mass ratio of glucose to tourmaline is 2:3; and the particle size of the tourmaline is less than 10000 mesh; (2) The dried product after the hydrothermal reaction is carbonized at a high temperature of 480-500° C. under the protection of an inert gas to obtain tourmaline with conductive carbon on the surface, which is a Fenton-like catalyst for the efficient reduction of Fe(III).

2. The preparation method according to claim 1, characterized in that: In step (1), the concentration of tourmaline in the mixed solution is 150-200 g L -1 .

3. The preparation method according to claim 1, characterized in that: In step (2), the inert gas is a rare gas and / or nitrogen.

4. The preparation method according to claim 1, characterized in that: In step (2), the heating rate of the high temperature carbonization is 5-10°C min -1 .

5. The preparation method according to claim 1, characterized in that: In step (2), the high temperature carbonization time is 2-3 hours.

6. Tourmaline having conductive carbon on its surface prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the tourmaline having conductive carbon on the surface according to claim 6 in reducing Fe(III).

Citation Information

Patent Citations

  • A one-step synthesis of hydrothermal carbon-supported ferrooxate and its preparation method

    CN113600238B

  • Carbon-coated SnO<2> hollow nanosphere composite material and preparation method therefor

    CN106099052A

  • Magnetic Fenton catalyst as well as preparation method and application thereof

    CN113318739A